Home range size and patterns of movement in Bornean Earless Monitors, Lanthanotus borneensis, in Sarawak, Borneo - Veronica, Leah; Pui, Yong Min; Indraneil, Das (Society for the Study of Amphibians and Reptiles, 2025)
Lanthanotus borneensis, Bornean Earless Monitors, are a species of conservation concern, categorized as Endangered in the International Union for Conservation of Nature Red List, and under the list of Totally Protected species in both Kalimantan and Sarawak. We applied radiotelemetry to a study of spatial ecology of nine adults of L. borneensis in Central Sarawak (four males, five females). Minimum convex polygons (100%) were generated for individuals to assess home range sizes. Home range sizes averaged 500.8 ± 300.9 m2, and only a slight overlap of space use was observed between sexes. L. borneensis are apparently sedentary for an average of 3 d, with intervening spikes of high movement, highest daily movement being 74 m. Our research demonstrates space use requirements of L. borneensis, which can be applied to conservation management efforts of this and similar tropical herpetofaunal species in Borneo.